Exploring the Predictive Power of Personal Demographic Factors on Conflict Management Styles A Study of Bank Employees in the Western Province in Sri Lanka - Chathurangi, T.D.N.; Padmasiri, W.D.T. (University of Sri Jayewardenepura, Nugegoda., 2014)
The aim of this research was to identify the influence of personal demographic variables on conflict management styles. It is necessary to identify the factors that influence individual’s conflict management styles to improve work place relations and productivity of individuals, but very few attempts have been made to find out the factors influencing the conflict management styles in Sri Lanka. In this present study, 161 respondents who were randomly selected from various banks in the western province were analyzed. The data obtained from the returned questionnaires were analyzed using the percentage distribution, mean, Correlation, Chi-square, T-test and One-way ANOVA. Analyses of the data indicated that only the gender has a significant influence on the conflict management styles of the bank employees. The findings further revealed that no significant difference was found between males and females. Moreover, no significant difference was found between the age groups. However,, there was significant difference between Christians and Hindus in preferring the collaborating style. Similarly, there was significant difference between married and unmarried employees on the competing style. Further, educational qualification also has significant difference on the competing style. Work experience has significantly differed in the compromising style.
Keywords: Conflict Management Styles; Demographic variables; Collaborating style; Competing style; Compromising style